Architecture Information Technology Master Plan for Development Framework of a Village Government - Suryanto, Tri Lathif Mardi; Wulansari, Anita; Billah, Mu'tasim; Ridwandono, Doddy (Nusantara Science and Technology Proceedings, 2023)
The objective of this study is to examine the problems related to Information Technology (IT) governance in Randegan Village and develop an IT Master Plan as a resolution. The primary objective is to enhance the quality of public services and optimize the functioning of village administration by implementing e-government principles and smart village concepts. The research methodology employed data collection techniques such as literature review, field survey, and interviews with key individuals from the village. The findings indicated that the level of IT governance in Randegan Village is currently restricted and not fully optimized. To address this difficulty, a comprehensive IT master plan was formulated using a combination of TOGAF, Zachman, and SPBE frameworks. The IT Master Plan for Randegan Village was developed using a four-stage approach. This approach involves identifying the needs of the village, evaluating public services, implementing IT solutions, and aligning with the SPBE concept. By implementing this strategy, the village is anticipated to enhance the caliber of public services, leading to a smart and technologically proficient village.